Hypercalciuria in Sarcoidosis: A Specific Biomarker With Clinical Utility - Cameli, Paolo; Caffarelli, Carla; Refini, Rosa Metella; Bergantini, Laura; d'Alessandro, Miriana; Armati, Martina; Tomai Pitinca, Maria Dea; Sestini, Piersante; Gonnelli, Stefano; Bargagli, Elena (Frontiers in Medicine, 2020)
Background: Changes in calcium metabolism are quite common in sarcoidosis: hypercalciuria is linked to a persistent clinical phenotype and more active disease. No data is yet available on the specificity of parameters of calcium metabolism as biomarkers for distinguishing different chronic interstitial lung diseases (ILD). Here we assessed calcium metabolism in an Italian population of sarcoidosis patients, which included a group with stage IV fibrotic disease, and compared the results with those of idiopathic pulmonary fibrosis (IPF) and chronic hypersensitivity pneumonitis (cHP) patients. Population and Methods: We recruited sarcoidosis, IPF and cHP patients retrospectively. All patients were diagnosed through multidisciplinary discussion and were monitored at the Regional ILD Referral Centre in Siena. Clinical, radiological, functional, immunological and laboratory parameters were collected and entered in an electronic database for data analysis. Results: A total of 305 patients (237 sarcoidosis, 40 IPF and 28 cHP) were enrolled. Sarcoidosis patients included a predominance of females and were significantly younger than IPF and cHP patients (p<0.0001 for both). In the sarcoidosis population, 17 patients (7.2%) showed radiological evidence of lung fibrosis, according the Scadding classification; fibrotic disease was also confirmed by CT scan. Concerning calcium metabolism, sarcoidosis patients showed significantly higher serum and urinary concentrations of calcium than IPF and cHP patients (p=0.0004 and p<0.0001, respectively). These findings were also confirmed when comparing groups with fibrotic sarcoidosis, IPF and cHP (p=0.0237 and p=0.0138). According to receiver operating characteristics (ROC) curve analysis, urinary calcium showed better diagnostic accuracy than serum calcium in discriminating sarcoid and non-sarcoid lung fibrosis (AUC 0.7658 vs 0.6205; p=0.0026 vs p=0.1820). Discussion: Our results confirmed that changes in calcium metabolism, particularly hypercalciuria, occur in a substantial percentage of patients with sarcoidosis. Higher serum and urinary concentrations of calcium were found than in IPF and cHP; the same results were observed when the comparison was limited to patients with fibrotic sarcoidosis, supporting the hypothesis that dysregulation of calcium metabolism may be a special feature of sarcoid granulomas. Hypercalciuria distinguished fibrotic sarcoidosis from IPF and cHP, suggesting that assessment of calcium metabolism may be useful in the diagnostic pathway of ILDs.